Advanced style : older & wiser - Cohen, Ari Seth (powerHouse Books, 2016)
This follow-up to the bestselling Advanced Style features more senior street style and inspiration from all over the globe. Similar in format to the original, with dozens of portraits from cities all over the world, this book also features 22 short essays by some of the portrait subjects, distilling the wisdom and lifestyle secrets of some of Cohen's favorite Advanced Style ladies.